The Davis discipline : - Rothchild, John (J. Wiley, 2001)
Books on successful Wall Street investors have become common currency in publishing. Here, Rothchild (One Up On Wall Street) examines the legendary Shelby Davis, who founded Davis Selected Advisors in 1947. Rothchild chronicles how over the years Davis, his son, and his grandchildren have created a literal "family of funds" generating enormous returns for their investors. Davis and his progeny were somewhat conservative in their investment philosophies. They chose insurance companies, banks, and other financial institutions to invest in for the long-term, and the returns were nothing short of astonishing. Unfortunately, much of the historical eyewitness accounts provided here seem leaden. This, combined with an almost pedestrian writing style and the author's often fawning attitude toward the Davis family, makes for a rather lightweight work.